The Optimization Of Bali Cattle Farming Business Production In Gorontalo - Supriyo Imran; Ria Indriani; Haris Singgili (Cita Konsultindo Research Center, 2024)
Bone Bolango Regency is one of the regencies in the Province of Gorontalo that serves as a center for the development of beef cattle, especially Bali cattle. Livestock feed availability is managed independently by farmers through cultivating forages, and livestock business management activities are carried out in livestock pens. This study aims to analyze the optimization of production and economic scale in Bali cattle farming businesses in Bone Bolango Regency. The method used was a survey. Purposive sampling was used to select respondents with consideration for farmers engaged in Bali cattle fattening businesses in Bone Bolango Regency, totaling 92 individuals. Data analysis was conducted using Cobb-Douglas production function analysis. The results show that 1) The production factor of feeder cattle is inefficient, requiring a reduction in quantity to achieve an optimal value of 86 kg cattle weight. The use of medications is inefficient and needs to be reduced to achieve an optimal value of 1,353.15 mg. Meanwhile, labor is not yet efficient, requiring an increase in production factors to reach an optimal value of 524.04 man-days. The feed production factor is already efficient, with the quantity being appropriate to achieve the optimization of Bali cattle production, which is 3,631 kg. 2) The economic scale of Bali cattle farming businesses in the Kabila District of Bone Bolango Regency is in a position of Decreasing Returns to Scale, as indicated by a return to scale value of less than one, which is 0.852. That implies that any increase in fixed inputs in the long term is always followed by a diminishing increase in output.